Normal weight obesity in adolescents: patterns and associated factors - Kaczmarek, Maria (Frontiers in Nutrition, 2025)
BackgroundNormal-weight obesity (NWO), which is defined as excess body fat despite a normal body mass index (BMI), is increasingly recognized as a cardiometabolic risk factor. However, data on its prevalence and associated factors in adolescent populations is limited.ObjectivesTo estimate the prevalence of NWO among Polish adolescents and to identify individual and contextual correlates using a multidimensional ecological framework.MethodsData were drawn from the cross-sectional, population-based ADOPOLNOR study and included 4,037 adolescents (49.6% boys) aged 10–18 years with a normal BMI, as classified by the International Obesity Task Force (IOTF). Body composition was assessed via bioelectrical impedance analysis. NWO was defined as a fat mass percentage (FM%) at or above the 85th percentile for age and sex, based on national reference values. Logistic regression was used to identify factors associated with NWO.ResultsThe prevalence of NWO was 16.5%, which was slightly higher in girls (17.3%) than in boys (15.8%). Adolescents with NWO had significantly higher FM%, fat mass index and fat-to-muscle mass ratio (p < 0.001; r ≈ 0.57–0.63), highlighting the limitations of BMI in detecting excess adiposity. Multivariate logistic regression analysis revealed that female sex (OR = 1.23, p = 0.046), older age (OR = 1.60, p = 0.014), family history of obesity (OR = 1.84, p = 0.003) and dieting for weight loss (OR = 1.81, p = 0.004) were risk factors for NWO. Protective factors included high family affluence (OR = 0.79, p = 0.017), high dietary quality (OR = 0.53, p < 0.001), regular mealtimes (OR = 0.65, p = 0.028) and high physical activity (OR = 0.53, p < 0.001).ConclusionNWO affects a significant proportion of adolescents and cannot be detected by BMI alone. Routine body composition assessment and the promotion of healthy behaviors are therefore essential for early identification and prevention.